HUBUNGAN ANTARA PENGETAHUAN DAN KINERJA KADER KESEHATAN - Rinayati Rinayati; Ambar Dwi Erawati; Sri Wahyuning (LPPM STIKES KENDAL, 2020)
In 2019 heahth program in Semarang tend to increase, The partnership between health workers and health cadres is important. The performance of health cadres in the community has essence that cannot be released with health service. Methods descriptive analytic with cross-sectional. Population all health cadres in the Gondoriyo region. samples 68 respondents. primary data obtained through direct interviews using a structured questionnaire.Analysis using uni variate analysis, frequency distribution and bivariate analysis using the Spearman Rank test. Result, good knowledge level (73,5%) ,good level cadre performance ( 73,5%) health cadre knowledge is not related to cadre performance (p value = 0.883 and r = 0.089.